Capacidade de absorção dos sinais capturados do ambiente para inovação : um estudo de casos em empresas industriais sergipanas do segmento de confecções têxtil - Souza, Shirley Andrade (2019)
The profound economic, social and technological transformation that has taken place over the years, together with the commercial opening of the country, has brought structural changes to the Brazilian industry. These changes have been even more significant for Brazilian textile manufacturing companies because they are inserted in a market that is highly dynamic, competitive, changing and with a strong presence of Asian products, which has required these companies to develop capacities to absorb the changes of the environment and generate innovation. In addition, these transformations have caused companies to increase the demand and the need to use their internal capabilities to monitor, capture and apply the signals that the environment emits on market trends or changes. In this sense, based on the assumptions that an organization's ability to survive depends on its ability to anticipate changes in its environment and that the capture of signals in the market provides information that enables companies to make decisions to innovate, The objective of this study is to describe and analyze the absorptive capacity (CA) of Sergipe industrial companies, from the textile segment, to the signals captured from the environment that indicate the need for innovation in response to changes in the environment. Marketplace. The research development is based on a model of multidimensional CA measurement supported by the proposal developed by Camisón and Fóres (2011). In order to carry out the research, a qualitative collection instrument was built, which was applied in seven companies with innovative characteristics compared to the local competition. The companies are micro to medium and develop innovations in process and marketing. The result shows that, from the perspective of managers, the industries analyzed seek to renew existing knowledge and assimilate external information to adapt and transform their organizational strategies. The exploration of knowledge takes place from the relations with clients and suppliers, previous knowledge of the leaderships and the existing structure in the organization. The companies that presented the best CA were those that faced direct competition, because their presence created incentives for the search for information to differentiate and become competitive.